2017
DOI: 10.1109/jlt.2016.2618618
|View full text |Cite
|
Sign up to set email alerts
|

A Fiber Optic Probe for Tumor Laser Ablation With Integrated Temperature Measurement Capability

Abstract: The paper presents the characterization results of a new all-optical applicator for improved tumor laser ablation treatments that features customized irradiation pattern and builtin temperature sensors. The probe exploits a double cladding optical fiber to integrate some Bragg gratings acting as temperature sensing elements in the core, while guiding the high power beam used for the ablation in the inner cladding. The assessment of the probe behavior has been conducted in two steps: first, with an agar gel pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…UV-laser light. In this manner, light can escape from the lateral surface in a controlled way (and not only from the tip as it happens in unmodified fibres), producing an almost cylindrical irradiation pattern [27]. An FBG (from Technica, Atlanta, GA, inscribed in the core of a standard telecom grade 125 mm-diameter fibre with polyimide coating, central wavelength of 1557.5 nm) was placed in contact with the delivery fibre in correspondence to the irradiated region in order to monitor the induced tissue temperature.…”
Section: Light Delivery and Fbg Sensing Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…UV-laser light. In this manner, light can escape from the lateral surface in a controlled way (and not only from the tip as it happens in unmodified fibres), producing an almost cylindrical irradiation pattern [27]. An FBG (from Technica, Atlanta, GA, inscribed in the core of a standard telecom grade 125 mm-diameter fibre with polyimide coating, central wavelength of 1557.5 nm) was placed in contact with the delivery fibre in correspondence to the irradiated region in order to monitor the induced tissue temperature.…”
Section: Light Delivery and Fbg Sensing Toolmentioning
confidence: 99%
“…The choice of the silica glass material (the same material as optical fibres) for this protective capillary is motivated by its low infra-red light absorption. The entire system is controlled by a custom-made LabVIEW (National Instruments, Austin, TX) software, which allows to monitor the laser status and to control parameters such as laser power and treatment time [27].…”
Section: Light Delivery and Fbg Sensing Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to this, the efficacy of using optical sensors for monitoring the temperature diffusion during a LA was recently demonstrated by many studies [92][93][94][95]. In 2017, Gassino et al developed a fully optical system for Tumor LA with an optical probe equipped with temperature real-time measurement using sensors based on Fiber Bragg Gratings (FBGs) [96]. The results obtained showed that the thermal pattern corresponds to the desired shape.…”
Section: Laser Ablationmentioning
confidence: 99%
“…1, in case of temperature gradients this simple relation provides a rough underestimation of the actual temperature along the grating length.This is particularly limiting in LITT since large temperature gradients due to the localized absorption of the laser beam or the presence of blood vessels could originate local underestimations, with subsequent risk of unpredicted carbonizations [15], [16]. III.…”
Section: Fbg Principlesmentioning
confidence: 99%